Validity of Carotid Doppler Ultrasound for Detection of Carotid Artery Plaque Keeping Computed Tomography Sensitivity as Reference Standard - Kanwal Rehana, Irsa Shuaib, Jansher Khan, Hina Gul, Nadia Khattak, Kalsoom Nawab, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the prevalence and specificity of arterial Doppler imaging pathology identification of artery blood vascular disease Study Design: Cross-sectional Place and Duration: In the department of Radiology, Peshawar Institute of Cardiology MTI, Peshawar for the duration from January 2022 to May 2022. Methods: Total 95 patients of both genders were presented. All the patients were suffering from ischemic cerebrovascular illness. Informed written consent of all the patients were taken for detailed demographics. Doppler ultrasound was performed in every patient by a consultant radiologist. Doppler ultrasound findings were compared with Carotid artery stenosis reports. SPSS 20.0 was used to analyze all data. Results: The mean age of the patients was 52.11±8.40 years and had mean BMI 24.1±13.25 kg/m2. The mean duration of disease was 1.7±6.34 years. 52 (54.7%) were males and 43 (45.3%) were females. There were 56 (58.9%) cases were smokers. Comorbidities were diabetes mellitus, ischemic heart disease, hypertension, ischemic stroke and dyslipidemia. Doppler ultrasound has a 91% overall sensitivity, 77% specificity, 47.3% positive predictive value, 92.5% negative predictive value, and 80% diagnostic accuracy. Conclusion: The accuracy of diagnosing Carotid artery stenosis has greatly increased over time because to technological innovation. The finding of additional measures to describe plaque susceptibility in the carotid artery has grown in importance, from monitoring the carotid artery's shrinking diameter to assessing the enhanced velocity field close to the obstruction/lesion site. The sensitivity, precision, and reliability of Artery stenosis diagnosis have improved because to computer-aided programmes used in a variety of imaging modalities. Keywords: Specificity, Carotid artery stenosis, Doppler ultrasound Sensitivity